Acupuncture and acupressure with improved cancer-related depression of retrospective studies - Wang, Feiqing; Zhao, Jianing; Li, Yanju; Yang, Xu; Wu, Dan; Yang, Bo; Zhang, Chike; He, Zhixu; Du, Liang; Zhu, Xiaodong; Ming, Dong; Liu, Yang; et al. (Frontiers in Oncology, 2022)
Acupuncture and acupressure used for treating cancer pain and depression and recognized as safe and effective by the international medical community. In this study, we systematically evaluated the efficacy and safety significance of acupuncture and acupressure in treating cancer-related depression. We searched MEDLINE, PubMed, Science Direct, Google Scholar, Web of Science and Embase and Chinese-language databases for randomized clinical trials (RCTs). To assess efficacy, rating scales administered by clinicians or experts were preferred, including the Hamilton Depression Rating Scale (HAMD), Self-rating Anxiety Scale (SAS), Self-rating Depression Scale (SDS), and Quality of Life Questionnaire-Core 30 (QLQ-C30) and the total effective rate after treatment. In all, Sixteen RCTs involving 1019 cancer patients were included in the Meta-analysis. Eleven (69%) of these studies reported the post-treatment total effective rate. Three hundred fifty-three patients received antidepressants; the total effective rate was 72.5%. Three hundred sixty-one patients underwent acupuncture and acupressure; the total effective rate was 90%. Meta-analysis results showed I2 = 0%, no heterogeneity, (Z = 5.84, p < 0.00001); and combined OR = 3.55, (95% CI = 2.32 to 5.43). This study found that acupuncture and acupressure are as effective as medication in the treatment of cancer-related depression (p ≤ 0.00001), provide a reliable basis for the clinical use of acupuncture to treat cancer-related depression, help promote nonpharmacological treatment for cancer-related complications. These approaches thus help reduce drug resistance and adverse reactions and improve patients’ quality of life.